Anti-Interleukin-6 Promotes Allogeneic Bone Marrow Engraftment and Prolonged Graft Survival in an Irradiation-Free Murine Transplant Model - Granofszky, Nicolas; Farkas, Andreas M.; Muckenhuber, Moritz; Mahr, Benedikt; Unger, Lukas; Maschke, Svenja; Pilat, Nina; Holly, Raimund; Wiletel, Mario; Regele, Heinz; Wekerle, Thomas (Frontiers in Immunology, 2017)
Transfer of recipient regulatory T cells (Tregs) induces mixed chimerism and tolerance in an irradiation-free bone marrow (BM) transplantation (BMT) model involving short-course co-stimulation blockade (CB) and mTOR inhibition. Boosting endogenous Tregs pharmacologically in vivo would be an attractive alternative avoiding the current limitations of performing adoptive cell therapy in the routine clinical setting. Interleukin-6 (IL-6) potently inhibits Treg differentiation and its blockade was shown to increase Treg numbers in vivo. We therefore investigated whether IL-6 blockade can replace adoptive Treg transfer in irradiation-free allogeneic BMT. Treatment with anti-IL-6 instead of Treg transfer led to multilineage chimerism (persisting for 12 weeks) in recipients of fully mismatched BM and significantly prolonged donor skin (MST 58 days) and heart (MST >100 days) graft survival. Endogenous Foxp3+ Tregs expanded in anti-IL-6 treated BMT recipients, while dendritic cell (DC) activation and memory CD8+ T cell development were inhibited. Adding anti-IL-17 to anti-IL-6 treatment increased Treg frequencies, but did not further prolong donor skin graft survival significantly. These results demonstrate that IL-6 blockade promotes BM engraftment and donor graft survival in non-irradiated recipients and might provide an alternative to Treg cell therapy in the clinical setting.